P66 Sarcopenia In Copd: Prevalence, Clinical Correlates And Response To Pulmonary Rehabilitation. (10th November 2014) - Jones, SE; Maddocks, M; Kon, SSC; Canavan, JL; Nolan, CM; Clark, AL; Polkey, MI; Man, WD-C
Abstract : Background: Sarcopenia is age-related loss of skeletal muscle mass leading to increased risk of physical disability, poor health status and death. Although sarcopenia is primarily an age-related condition, it is recognised that there are multiple contributing factors, notably from immobility and the effects of chronic disease. International consensus working groups have defined sarcopenia as a loss of muscle mass and reduced muscle strength or function. Although skeletal muscle dysfunction is well recognised in chronic obstructive pulmonary disease (COPD), the prevalence of sarcopenia (defined using international consensus guidelines) and the impact of sarcopenia upon functional capacity and health related quality of life (HRQoL) have not been previously described in patients with COPD. Furthermore, it is not known whether sarcopenia affects the response to pulmonary rehabilitation (PR). Methods: Sarcopenia was determined using the European Working Group on Sarcopenia in Older People (EWGSOP) algorithm in 622 outpatients with stable COPD. Other measurements included incremental shuttle walk (ISW), five-repetition sit-to-stand (5STS), quadriceps maximum voluntary contraction (QMVC) and HRQoL (St George's Respiratory Disease (SGRQ) and COPD Assessment Test (CAT)). Response to PR was determined in 43 patients with sarcopenia and compared with a control group identified using propensity score matching. Baseline characteristics and change pre- to post-PR were compared between groups. Results: Prevalence of sarcopenia was 14.5% (16.1% men and 12.3% women; p = 0.20), which increased with advancing quartiles of age and GOLD spirometric stage. Patients with sarcopenia were older, had worse air flow obstruction, reduced QMVC, exercise capacity and HRQoL (Table 1 ). Both sarcopenic patients and controls showed significant improvements in exercise capacity, functional performance, QMVC and HRQoL with PR, with no between group differences. Following PR, 12/43 (28%) patients no longer met EWGSOP criteria for sarcopenia. Conclusion: There is a high prevalence of sarcopenia in patients with COPD which is associated with reduced exercise capacity and HRQoL. Sarcopenia does not impact upon response to pulmonary rehabilitation in COPD.